1991
DOI: 10.1007/bf02053691
|View full text |Cite
|
Sign up to set email alerts
|

Survival after resection of carcinoma of the splenic flexure

Abstract: Nine hundred ten patients undergoing colectomy for colon cancer were studied retrospectively. Seventy-four cancers (8 percent) were located at the splenic flexure. The stage at presentation was no different between splenic flexure cancers and colon carcinomas at other sites. Although splenic flexure cancers had twice the incidence of obstruction as did other colon cancers and obstruction in the overall series adversely affected survival, there was no difference in survival between splenic flexure cancer patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
60
2

Year Published

1998
1998
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(63 citation statements)
references
References 4 publications
0
60
2
Order By: Relevance
“…Cancer of splenic flexure is rare, comprising only 2% to 5% of all colorectal cancers (7)(8)(9)(10). Very few studies have specifically investigated the use of laparoscopic left hemicolectomy for cancer (11).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cancer of splenic flexure is rare, comprising only 2% to 5% of all colorectal cancers (7)(8)(9)(10). Very few studies have specifically investigated the use of laparoscopic left hemicolectomy for cancer (11).…”
Section: Discussionmentioning
confidence: 99%
“…Some surgeons have argued that subtotal colectomy or extended right hemicolectomy improves oncological outcome (7,13). However, other studies have demonstrated that the prognosis for left hemi-colon cancer is no worse than for other colon cancers, and that left hemi-colectomy is sufficient for a satisfactory oncological outcome (8,9,14). A recent study showed that complete mesocolic excision in the mesocolic plane with central vascular ligation is associated with the removal of more mesocolon and a greater lymph node yield, and might improve 5-year survival (15).…”
Section: Discussionmentioning
confidence: 99%
“…Other investigators have suggested left partial colectomy, with ligation of both the left branch of the middle colic artery and the left colic artery at their origins to remove nodes likely to be involved [11]. On the other hand, Levien et al [1] demonstrated that SF cancers are not associated with a worse prognosis than other colon cancers and that dual lymphatic drainage does not confer a survival disadvantage, so extended resection is unnecessary.…”
Section: Discussionmentioning
confidence: 99%
“…Accounting for approximately 3 to 8% of all colon cancers, it is associated with a high risk of obstruction and poor prognosis [1,2]. Treatment for SF carcinoma is considered challenging and not fully standardized [3].…”
mentioning
confidence: 99%
“…The concept of high vessel ligation is to include resection of the paracolic nodes, intermediate nodes and apical lymphnodes, which defined as D3 lymph-adenectomy. D3 lymph-adenectomy have been widely used and accepted in Japan, China and Korea [10][11][12]. In case of SFC, whether high level of vessel ligation is required to include LMC artery or not, yet has not been proposed.…”
mentioning
confidence: 99%